Amelioration of spinal cord injury in rats by blocking peroxynitrite/calpain activity - Khan, Mushfiquddin (BMC Neurosci, 2018)
BACKGROUND: Spinal cord injury (SCI) is one of the leading causes of disability and chronic pain. In SCI-induced pathology, homeostasis of the nitric oxide (NO) metabolome is lost. Major NO metabolites such as S-nitrosoglutathione (GSNO) and peroxynitrite are reported to play pivotal roles in regulating the activities of key cysteine proteases, calpains. While peroxynitrite (a metabolite of NO and superoxide) up regulates the activities of calpains leading to neurodegeneration, GSNO (a metabolite of NO and glutathione) down regulates the activities of calpains leading to neuroprotection. In this study, effect of GSNO on locomotor function and pain threshold and their relationship with the levels of peroxynitrite and the activity of calpain in the injured spinal cord were investigated using a 2-week rat model of contusion SCI. RESULTS: SCI animals were initially treated with GSNO at 2 h after the injury followed by a once daily dose of GSNO for 14 days. Locomotor function was evaluated by “Basso Beattie and Bresnahan (BBB) locomotor rating scale” and pain by mechanical allodynia. Peroxynitrite level, as expression of 3-nitrotyrosine (3-NT), calpain activity, as the degradation products of calpain substrate alpha II spectrin, and nNOS activity, as the expression phospho nNOS, were measured by western blot analysis. Treatment with GSNO improved locomotor function and mitigated pain. The treatment also reduced the levels of peroxynitrite (3-NT) and decreased activity of calpains. Reduced levels of peroxynitrite resulted from the GSNO-mediated inhibition of aberrant activity of neuronal nitric oxide synthase (nNOS). CONCLUSIONS: The data indicates that higher levels of 3-NT and aberrant activities of nNOS and calpains correlated with SCI pathology and functional deficits. Treatment with GSNO improved locomotor function and mitigated mechanical allodynia acutely post-injury. Because GSNO shows potential to ameliorate experimental SCI, we discuss implications for GSNO therapy in clinical SCI research.